Towards the Establishment of Spouse Tort Liability within Marriage - Wang, Ruitong (Transactions on Social Science, Education and Humanities Research, 2024)
In the evolution of law, there is a growing awakening of individual consciousness. The number of intra-marital tort claims not predicated on divorce has increased in judicial practice. However, China currently only has a compensation system for damages arising from divorce, which is not conducive to the protection of the legitimate rights and interests of the parties involved. With the development of the economy, the liberalization of ideas, the collision of Chinese and Western legal thoughts, and the independent status of marital economics, the establishment of an intra-marital tort system has become possible. Intra-marital tort litigation is not predicated on the termination of marriage, but is established to protect the victim, punish the at-fault party, and prevent the occurrence of tortious acts. The elements of such litigation should have stricter requirements than general torts.